Pelatihan al-Asma al-Husna Metode Hanifida: Solusi Nyata Lejitkan Otak Anak (Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
The age of 1 to 5 years is a golden age for children, this is the time for the task of parents as the first teacher to maximize all the potential that exists in the child, at this stage gross motor, fine cognitive and social interaction will develop and grow rapidly. However, many parents do not have free time and in the end the children are sent to Kindergarten (TK) schools. With the al-Asma al-Husna Hanifida method in kindergarten, it has a tremendous impact, not only can children pronounce asthma’, but with this method children will be invited to move, express and imagine. The method of implementing this service activity is divided into three stages, namely, needs analysis, implementation and assistance. This training was attended by Kindergarten teachers throughout the Turi Lamongan sub-district (IGTKM) as many as 150 participants. This training begins with the dynamics of turning the brain on, giving material by the trainer, practicing, evaluating and reflecting.